Therapeutic combination of catheter-directed thrombolysis, rheolytic thrombectomy and percutaneous transluminal angioplasty in acute on chronic limb ischemia: a case report - Erina Febriani Widiastari; Gary Pradhana; Marolop Pardede (Indonesian Vascular Access Association (IVAA), 2022)
Background: Acute limb ischemia (ALI) is a sudden decrease in leg perfusion that threatens the viability of the limb with symptom onset within 2 weeks. In peripheral artery disease (PAD) conditions, occlusion of blood vessels can occur due to thrombosis or atherosclerotic plaque embolism, which is called